The effect of incompatible plant pathogens on the host plant - Al-Ani, Laith Khalil Tawfeeq; Furtado, Edson Luiz [UNESP] (Elsevier, 2020)
The avirulent strain of plant pathogens is spreading and living with a virulent strain of plant pathogen on the host or nonhost plant in the fields. The existence of many strains of plant pathogens, living in one niche leads the interaction among them. This interaction includes two kind, (A) Antagonism, and (B) Synergism. The useful role of avirulent or nonpathogenic strain is by showing the ability to antagonistic against virulent strain by many mechanisms. While the opposite side of avirulent or incompatible strain forms a harmful role through cooperation with virulent strain in the colonization of the host plant. This cooperation may contribute to the occurrence of the plant disease epidemic. There is mutual benefit happening between incompatible strain and virulent strain of plant pathogens. In conclusion, the mixing among strains of the plant pathogens may lead to prominence a new virulent strain that is more destructive for the plants.
Keywords: Avirulence; Biological control; Cross-protection; Cutinase; Hypovirulence; Nonpathogen; Plant defence; Plant disease epidemic